2012
DOI: 10.4103/2230-8210.98011
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Nigerians with diabetes mellitus - Diabcare Nigeria study group (2008): Results of a multicenter study

Abstract: Background:Diabetes Mellitus is the commonest endocrine-metabolic disorder in Nigeria similar to the experience in other parts of the world. The aim was to assess the clinical and laboratory profile, and evaluate the quality of care of Nigerian diabetics with a view to planning improved diabetes care.Materials and Methods:In a multicenter study across seven tertiary health centers in Nigeria, the clinical and laboratory parameters of diabetic out-patients were evaluated. Clinical parameters studied include typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
84
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(112 citation statements)
references
References 16 publications
23
84
5
Order By: Relevance
“…The higher percentage of females recorded here more than males Table 1 is striking and agrees with the study of Ogunbodede et al [11] who gave a higher female to male ratio in his study. Also, Chinenye et al [12] in a multi-center study in Nigeria reported a ratio of 2:1, female: male ratio of diabetic patients; however, these results do not reflect the pattern observed in other studies involving diabetic patients with periodontal diseases outside the tertiary health centers in Nigeria where the male: female ratio is reported to be close to 1:1 [13][14][15].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The higher percentage of females recorded here more than males Table 1 is striking and agrees with the study of Ogunbodede et al [11] who gave a higher female to male ratio in his study. Also, Chinenye et al [12] in a multi-center study in Nigeria reported a ratio of 2:1, female: male ratio of diabetic patients; however, these results do not reflect the pattern observed in other studies involving diabetic patients with periodontal diseases outside the tertiary health centers in Nigeria where the male: female ratio is reported to be close to 1:1 [13][14][15].…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, Kapp et al [21] reported that respondents with diabetes showed a considerably higher prevalence of tooth loss of up to 5 and 6 or more teeth, compared with no tooth loss in non-diabetic respondents. Studies in a Nigerian population in Ile-Ife reported that the mean number of missing teeth was higher for diabetic subjects 1.56 ± 2.39, than the non-diabetic subjects 0.96 ± 1.64 [11]. The reason for these higher number of tooth loss in diabetic patients has been attributed to a lack of knowledge of the undesirable bi-directional relationship between diabetes mellitus and periodontal disease such that hyperglycemic environment will result in periodontal disease and periodontal disease on the other hand, will increase insulin resistance which could lead to tooth loss if left unchecked [1,22].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we found that only one study conducted in Nigeria reported on the use of home blood glucose monitoring (HBGM) devices. In this cohort of 531 diabetic patients receiving care in an urban setting, only 27.2% had access to HBGM 11. It was not reported whether this translated in a better outcome of care or not.…”
Section: Prevention and Control Of Diabetes And Obesity In Africamentioning
confidence: 87%
“…A lifetime risk as high as 15 to 25 % has also been reported [11,12]. The prevalence of DFU among diabetic patients varies widely from about 14.8 % in Ethiopia to 21.2 % in Calabar, Nigeria [13][14][15][16]. In Lagos, Nigeria, Ogbera et al [17] found a high prevalence of 41.5 % for DFU.…”
Section: Introductionmentioning
confidence: 92%